2002
DOI: 10.4049/jimmunol.168.7.3512
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Regression Induced by Intratumor Therapy with a Disabled Infectious Single Cycle (DISC) Herpes Simplex Virus (HSV) Vector, DISC/HSV/Murine Granulocyte-Macrophage Colony-Stimulating Factor, Correlates with Antigen-Specific Adaptive Immunity

Abstract: Direct intratumor injection of a disabled infectious single cycle HSV-2 virus encoding the murine GM-CSF gene (DISC/mGM-CSF) into established murine colon carcinoma CT26 tumors induced a significant delay in tumor growth and complete tumor regression in up to 70% of animals. Pre-existing immunity to HSV did not reduce the therapeutic efficacy of DISC/mGM-CSF, and, when administered in combination with syngeneic dendritic cells, further decreased tumor growth and increased the incidence of complete tumor regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 33 publications
7
37
0
Order By: Relevance
“…Similarly, using OX40R monoclonal Ab, the induced GL261 glioma regression in B6 mice was also found to be dependent on both CD4 + and CD8 + (Kaergaard et al, 2000). These results are consistent with our previous observation that both T-cell populations are involved in tumour rejection following therapy of established tumours with DISC/mGM-CSF (Ali et al, 2000(Ali et al, , 2002.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similarly, using OX40R monoclonal Ab, the induced GL261 glioma regression in B6 mice was also found to be dependent on both CD4 + and CD8 + (Kaergaard et al, 2000). These results are consistent with our previous observation that both T-cell populations are involved in tumour rejection following therapy of established tumours with DISC/mGM-CSF (Ali et al, 2000(Ali et al, , 2002.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that direct intra-tumour injection of subcutaneous CT26 tumours with DISC/mGM-CSF induces the complete regression of tumours in a proportion of treated animals (Todryk et al, 1999;Ali et al, 2002). In the present investigation the effect of combination therapy of mOX40L fusion protein and DISC/mGM-CSF therapy on established subcutaneous 4T1 and CT26 tumours was determined.…”
Section: Combination Therapy Of Ox40l and Disc/mgm-csf Virusmentioning
confidence: 68%
“…1,22 Tumor regression was correlated with the potency of CTL activity, and in the present study, we demonstrate that the adoptive transfer of antigen-specific CTLs i.v. into mice with established experimental lung metastasis significantly increased the overall survival in comparison to control animals.…”
Section: Rolling and Flying Cellssupporting
confidence: 75%
“…1 Splenocytes from regressor mice but not progressor or naive mice have demonstrated potent AH-1 peptide-specific CTL activity following in vitro stimulation (data not shown). 1 …”
Section: Inhibition Of Ct26 Tumors By Direct Intratumor Injection Witmentioning
confidence: 99%
See 1 more Smart Citation